The Analysis of the Target Component of Law Interpretative Activities - Terekhov, Evgeniy (Legal Concept = Pravovaya Paradigma, 2017)
Introduction: law interpretative activities are an independent kind of legal activities, however, on a par with law-making and law enforcement they have not been investigated properly in the contemporary legal science. Law interpretative activities are to be regarded as a mechanism that is supported by having goals, an object, methods, subjects, principles, functions, varieties in their structure; therefore, in this work the author sets the task to explore their targets. Methods: the methodological framework for this study is a set of scientific methods, among which the main place is occupied by the methods of historicism, systematicity, analysis and the comparative law method. A particular attention is drawn to the static and dynamic methods in the consideration of law interpretative activities. Results: grounded in the work the author’s position is based on the law and the authoritative scientists’ opinions on the issue of establishing goals of law interpretative activities; the evolutionary nature of the process of interpreting the rules of law are taken into account. Conclusions: the study has identified a relevant goal of modern law interpretative activities. It is established that the fundamental goal of modern law interpretative activities is to discover the meaning of the rules of law, due to the economic, political, social, and cultural changes occurring in the society that are taken into consideration by the subjects of law interpretative activities when publishing the acts of the interpretation of the law. Therefore, it should be noted that the need for establishing the will of the legislator is evolutionarily behind the times and is not a real goal for law interpretative activities.